RELATION BETWEEN PORE MODEL AND CENTER-LINE TEMPERATURE IN HIGH BURN-UP UO2 PELLET - Suwardi Suwardi (Universitas Gadjah Mada, 2007)
Relation between pore model and center-line temperature of high burn up UO2 Pellet. Temperature distribution has been evaluated by using different model of pore distribution. Typical data of power distribution and coolant data have been chosen in this study. Different core model and core distribution model have been studied for related temperature, in correlation with high burn up thermal properties. Finite element combined finite different adapted from Saturn-1 has been used for calculating the temperature distribution. The center-line temperature for different pore model and related discussion is presented.